Dessabank, Lembaga Keuangan Masa Pemerintah Hindia Belanda di Pedesaan Buleleng-Bali, Awal Abad XX - Sidemen, Ida Ayu Wirasmini (Humanis, 2024)
The Dutch East Indies Government’s view of traditional financial management was an early attempt by the government to establish a network of modern financial institutions in rural areas. The government introduced Dessabank as a modern financial institution whose operational task is under the supervision or guidance of central cash officers. Dessabank as a banking institution has to follow the system of rural financial management. The establishment of Dessabank Patemon in 1914 in Patemon Village, Pengastulan District, Buleleng, was responded by the villagers through village officials and utilized the regulations (awig-awig) of Patemon Village. The Dessabank in Banjar Buleleng utilized local administrative personnel and The Dutch East Indies government expected the Dessabank will function well and meet the needs of the village community. In the villages where a Dessabank has been successfully established, there were successful stories such as; the setting of interest rates, the obligation to repay the loan principal, the introduction of the difference in the number of days between the Saka year and the Gregorian year, and the involvement of villagers as bank employees.